Smoking Cessation Considerations for People with Multiple Sclerosis - Christian Brooker; Myla Goldman; Sharon Tingen (University of Minnesota Libraries Publishing, 2020)
Background: Comprehensive care of people with multiple sclerosis integrates disease modifying therapy, symptom management and minimization of risk factors for disease progression. Cigarette smoking is a modifiable risk factor associated with development and progression of disease and increased disability. However, little is known about specific factors that affect smoking cessation in patients with multiple sclerosis or how to integrate smoking cessation into specialized multiple sclerosis care. Methods: Twenty-nine active smokers with multiple sclerosis were surveyed at the James Q. Miller Multiple Sclerosis clinic at the University of Virginia Health. Demographics, smoking history, multiple sclerosis history, interest in quitting, barriers to quitting and cessation modalities of interest were collected, specifically interest in working with a clinical pharmacist for cessation. Results: Seventy-six percent of individuals believed that there was no relationship between smoking and MS diagnosis and 52% were unaware of any relationship between smoking and disease progression. Less than half of patients (41%) reported receiving counseling from a primary care physician or neurologist about the importance of smoking cessation. Common barriers to quitting included enjoyment of smoking (76%) and cravings (55%). Seventy-six percent of patients expressed interest in utilizing pharmacotherapy and 37% were interested in working closely with a clinical pharmacist. Conclusions: It is critical that providers caring for patients with multiple sclerosis assess smoking status and educate smokers about the relationship between smoking and disease progression. Efforts should be made to better understand patient-specific barriers to quitting and preferred methods of treatment, including pharmacotherapy and behavioral therapy. A multidisciplinary approach to smoking cessation that includes a clinical pharmacist may aid in the development of individualized care plans with frequent monitoring to improve patient success.   Article Type: Case Study